Does Exchange Rates Swings Affect Trade? Evidence from an Emerging Open Economy - Gbadebo, Adedeji Daniel (International Journal of Economics and Financial Issues, 2023)
The volatility of the exchange rate is commonplace for every open economies. If excessive, it would have severe implications for the country’s international trades. Using the ARDL and cointegration bound tests on quarterly data [2000:Q2–2022:Q3], the study empirically explore how exchange rate volatility and other macroeconomic variables impacts real exports and imports demands for Nigeria. The evidence identify cointegration and the trade’ parsimonious models disclose a negative as well as significant short run effects of the exchange rate volatility. The estimated convergence ECM regressions indicate that exchange rates volatility cause significant decline in real exports and imports in the long run. Under this circumstance, the study supposes measures that will curb fluctuations beyond economic fundamentals. In particular, monetary authority should expand periodic exchange rate intervention to curtail excessive swings. This should be maintained intuitively and regularly appraise to avoid creating any counter-productive response.